An Ultrasound-Based Non-Invasive Blood Pressure Estimation Method Based on Optimal Vascular Wall Tracking Position - Liyuan Liu; Xingguang Geng; Fei Yao; Yitao Zhang; Haiying Zhang; Yunfeng Wang; Zhaoying Zheng (IEEE Access)
This study presents, for the first time, an ultrasound method combining focused and single plane wave transmissions to achieve single calibration, non-invasive, cuffless blood pressure monitoring. High-quality echo signals obtained from focused transmissions were first used to identify the optimal segment of the radial artery wall. Then, single plane wave signals were utilized to track this segment frame-by-frame and calculate local pulse wave velocity (PWV). Finally, the M-K equation was applied to estimate systolic and diastolic blood pressures. To validate the effectiveness of the proposed algorithm, 25 volunteers participated in the study. Data were collected using both an oscillometric cuff-based blood pressure monitor and our ultrasound system in four states: morning, evening, pre-exercise, and post-exercise. A total of 300 sets of comparative data were obtained. The overall mean deviation for systolic blood pressure was $2.2~± ~2.1$ mmHg, and for diastolic blood pressure, it was $2.1~± ~2.2$ mmHg. To our knowledge, this is the first study to achieve real-time blood pressure calculation within seconds using a single-array ultrasound transducer. Compared to existing non-invasive continuous blood pressure monitoring methods, this approach is faster and provides more accurate vascular wall information. Significance: Combined with affordable hardware, this method holds significant potential for the development of wearable devices for real-time cardiovascular health monitoring.